Reviews - V., Berit; Skov, Hans; Dahlgren, Mikael (Journal of Danish Archaeology, 1997)
Reviews: Michael A. Jochim: A Hunter-Gatherer Landscape. Southwest Germany in the Late Paleolithic and Mesolithic (by Berit V. Eriksen) Hjermind, M. Iversen & H. Krongaard Kristensen (eds.): Viborg Søndersø 1000-1300. Byarkæeologiske undersøgelser 1981 og 1984-85 (by Hans Skov) Anne Nørgård Jørgensen & Birthe L. Clausen ( eds.): Military Aspects of Scandinavian Society in a European Perspective (by Mikael Dahlgren)